Development of a Microbiology Practical Guide Based on Augmented Reality Technology on Virus Material - Meti Herlina; Apriza Fitriani; Rukiah Lubis (STAI Hubbulwathan Duri, 2024)
This study aims to develop an Augmented Reality (AR)-based Microbiology practicum guide to enhance learning quality and student engagement. AR technology facilitates understanding by presenting interactive 3D images and videos, making complex concepts like viruses more accessible and engaging for students. The research follows a Research and Development (RD) methodology comprising three stages: define, design, and develop. The practicum guide was created using vuforia, Blender 3D, Unity, and Photoshop software. A marker was designed to connect the AR components with 3D models for Android devices and incorporated into a printable guide. Validation results classify the AR-based practicum guide as highly valid, with overall validity reaching 85.8%. Specific aspects scored as follows: content (87.5%), presentation (85.7%), practicality (83.3%), language (85%), and media (87.5%). Student and lecturer responses also rated the guide as good, emphasizing its effectiveness in facilitating concept visualization and independent learning. The AR-based practicum guide significantly improves learning quality by motivating students, enabling real-life object visualization, and simplifying abstract concepts. This approach demonstrates the potential of AR technology to transform microbiology education and beyond. The developed AR-based Microbiology practicum guide is valid, effective, and tested, offering a modern, interactive approach to education. Its applications extend beyond microbiology, with potential use in disciplines like agriculture, architecture, and health sciences.